I stood on the shoulders of giants - V. A. Karlov (Эпилепсия и пароксизмальные состояния)
The author dedicated the article to the outstanding scientific achievements of his mentors, who represented the Moscow Neurological School founded by Dr. E.K. Sepp and Dr. M.B. Zucker, and accompanied his story with invaluable personal memories about their everyday scientific and clinical practice and personal human qualities. It also demonstrated how the fundamental concepts put forward by Dr. E.K. Sepp were developed and expanded by his students by using modern research methods.